Feasibility and Efficacy of an Addiction Treatment Program in Patients With Upper Aerodigestive Tract Cancer. (1st January 2014) - Perney, Pascal; Duny, Yohan; Nalpas, Bertrand; Lallemant, Benjamin; Rigole, Hélène; Cartier, César; Garrel, Renaud; Azria, The Addict-ORL Study Group (David; Blanc, François; Duhamel, Olivier; Neka, Meissa; Ichou, Marc; et al.
Abstract : Background : Continuing to smoke or to drink after the treatment of an upper aerodigestive tract (UADT) cancer is known to worsen the prognosis. We assessed the feasibility and efficacy of an addiction treatment program integrated into the cancer treatment. Method : In four units devoted to UADT tumors, we proposed an addiction treatment to all patients still drinking or smoking at the end of the cancer treatment; the abstinence rate was assessed 6 and 12 months later. Results : One hundred and sixteen patients were included. Among the 73 patients still drinking and/or smoking at the end of the cancer treatment, 46.6% accepted an addiction treatment. In the latter, abstinence rate was increased, 52.2% versus 31.03% (  p = .07) at M12. In patients both drinking and smoking, addiction treatment doubled the rate of abstinence of both products (31% vs. 14%). Conclusion : Offering addiction treatment to patients with UADT cancer improves abstinence rate and helps maintain long-term withdrawal.